Hemangioma and port-wine stain. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
Hemangioma and port-wine stain. Hemangioma on port-wine stain at the age of 3 months. At the age of 14 months hemangioma is involuting, whereas port-wine stain is unchanged.